Echoes of Rebellion: The Living Memory of DI/TII (1953-1965) and Its Ideological Transmission in South Sulawesi - Ahmad Subair (Journal of Innovative and Creativity, 2026)
This research is motivated by the phenomenon of the resurgence of narratives and symbols of the DI/TII movement led by Kahar Muzakkar (1953–1965) in contemporary religious discourse in South Sulawesi. This study addresses analytical gaps by exploring the dimension of collective memory as a bridge connecting historical rebellion with contemporary radicalism. Using the Systematic Literature Review (SLR) method, this study analyses historical and contemporary sources to trace the mechanisms of memory transmission. The findings reveal that the memory of DI/TII is preserved as a ‘living memory’ transmitted through three main channels: family and kinship networks, certain Islamic boarding schools that sacralize the narrative, and the circulation of literature and digital media. This memory is then activated by ‘memory entrepreneurs’ who align it with contemporary grievances and ultimately fuses with transnational jihadist ideology through a process of glocalization. The implication is that counter-terrorism approaches need to shift towards inclusive and reconciliatory memory politics.